Efficiency in Reducing Turbidity and TSS (Total Suspended Solid) Level Using Biocoagulant of Tamarind Seeds by Adjusting Raw Water pH - Ferry Kriswandana; Abrelian Ari Ratmansyah; Marlik Marlik (Aloha International Journal of Health Advancement (AIJHA), 2020)
Tamarind seeds can be used as coagulant because they contain protein that have role as polyelectrolytes. Optimum dose of tamarind seeds as coagulant material to reduce turbidity and TSS level in raw water (river water) had been researched previously, which was 1000 mg / L without noticing more on pH of river water that was used during the coagulation process. Furthermore, the purpose of this study was in order to investigate differences in the efficiency of biocoagulant of tamarind seeds in dose of 1000 mg / l for reducing turbidity and TSS level in raw water based on pH treatment. This research was a pre-experimental research with one group pre-posttest design. Subjects in this research were tamarind seeds as coagulant, meanwhile, the object in this research was raw water of Jagir River. This research used three variations of treatment for pH conditions, which were: acidic (pH 4), neutral (pH 7), and alkaline (pH 10) with coagulant doses of tamarind seeds each treatment in 1000 mg / L. Each treatment was replicated 9 times. The data that was obtained in this research was examined by calculating the efficiency in reducing turbidity and TSS levels, paired t-test statistical test, one-way anava test, and probit test. Moreover, result of this research showed that the best efficiency in reducing turbidity and TSS level by using coagulant of tamarind seeds in dose of 1000 mg / l was by treating acidic conditions (pH = 4), thus, it resulted efficiency value in reducing turbidity and TSS level for 94.56% and 83.78%. Result of paired t-test showed that there was a significant difference in the average of turbidity and TSS level before and after treatment. Result of one-way anava test showed that there was a significant difference in the average of efficiency in reducing turbidity and TSS level between treatment of acidic condition (pH = 4) and neutral conditions (pH = 7) and alkaline conditions (pH = 10). Result of probit test showed expectation of efficiency in reducing turbidity and TSS level in 85% and it required optimum pH values in 4.268 (acid) and 3.417 (acid). All in all, old tamarind seeds could be used as tamarind seed powder. Thus, it could be used as a coagulant material in order to purify water that was more efficient relatively and eco friendly. Keywords: pH; coagulant, tamarind seeds; efficiency